2015
DOI: 10.1590/s1516-89132015060304
|View full text |Cite
|
Sign up to set email alerts
|

Enteromorpha intestinalis Derived Seaweed Liquid Fertilizers as Prospective Biostimulant for Glycine max

Abstract: In the present study, the potential of seaweed liquid fertilizer (SLF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The value of macroalgae as fertilizers or biostimulants of plant growth results from the content of macroelements, trace elements, and other metabolites. These compounds are necessary for the plants growth and enhancement . Therefore, it can be assumed that produced from macroalgae extract will be a concentrated form of biologically active compounds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The value of macroalgae as fertilizers or biostimulants of plant growth results from the content of macroelements, trace elements, and other metabolites. These compounds are necessary for the plants growth and enhancement . Therefore, it can be assumed that produced from macroalgae extract will be a concentrated form of biologically active compounds.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of algal extracts, generally they stimulate the seeds germination, but it depends on many factors such as algae species, extraction method, concentration and chemical composition of extract, method of application, plant species, etc. The range of concentrations of algal extracts used in germinations tests is very wide, from very low, for example, 0.2, 0.4, and 1% for tomato and 0.2, 0.4, 0.6, 0.8, and 1% for mung bean , to much higher, for example, 2.5, 5, 7.5, 10, 12.5, and 15% for soybean ; 5, 10, 20, 30, 40, 50, and 100% for cowpea ; 20, 40, 60 and 100% for soybean . In the literature it was shown that seeds treated with lower concentrations of algal extracts exhibited higher germination rates and germination percentage, while the higher extracts concentrations inhibited the germination, for example, above 40% for cowpea , above 0.01% for tomato and lettuce .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with literature data, which confirm the positive effect of algal extracts on the growth and performance of soybeans. Mathur et al [58] tested the effect of green seaweed -Enteromorpha intestinalis derived liquid fertilizer as a biostimulant for Glycine max (L.) Merr. It was found that 60% of the algal extract (among tested concentrations -20, 40, 60 and 100% and control groups -water and chemical fertilizer) positively influenced seed germination, root and shoot length, the content of carbohydrates, proteins and pigments.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies pertaining to plant growth-promoting effects of seaweed have been reported by Shimaa et al (2016). In fact, the plant growth-promoting seaweed substances in Arabidopsis influence the biosynthetic pathways of phytohormones in plants (Jithesh et al, 2012) and a rich amount of auxin, gibberellins, cytokinins and antibiotics boost the growth and yield of soyabean (Mathur et al, 2015). Pacholczaket al (2016) have proven that in nine bark stem cuttings (Physocarpusopulifolius), the seaweed was the novel source of antioxidants and plant hormones osmoprotectants, plant nutrients and also bioactive metabolites of pharmaceutical and industrial significance.…”
mentioning
confidence: 99%